Society and Law During the SARS-COV-2 Health Crisis – Legal Thinking Issues and Normative Syntheses - Roghină, Răzvan Cosmin (Journal of Legal Studies, 2022)
In this paper, we aim to observe, from a bird's eye view, the meaning for which law dictates behaviors molded on values naturally hierarchized. The right to life is the absolute value that maintains its central position in any axiological hierarchy. Of course, we refer to the typology of societies connected to democratic and liberal values (more or less accentuated). We propose an approach with philosophical accents while traveling through the sphere of international regulations that protect rights and freedoms. All these will be related to the SARS-CoV-2 pandemic context. We will pay attention to the Romanian political praxis and constitutional justice during the health crisis. Finally, we will explore some legal and social thinking landmarks about what it means to approach a health crisis when it comes to understand and value freedom within the human existence coordinated by law.